Imaging of Liver Metastases - Wagle, Pratik; Ananthakrishnan, Lakshmi; Coppa, Christopher P. (Digestive Disease Interventions, 2017)
The evaluation of liver metastases using computed tomography (CT), magnetic resonance (MR) imaging, and positron emission tomography-CT (PET-CT) is discussed in this article. PET-MR and multienergy CT are newer techniques gaining appeal in the assessment of liver metastases and have also been reviewed.
Keywords: liver metastases; computed tomography; magnetic resonance; positron emission tomography; multienergy CT